THE CONDITION OF THE DENTAL HARD TISSUES IN PATIENTS WITH MENTAL ILLNESS - Otabek M. Astanov (Central Asian Journal of Medicine, 2024)
This study focuses on the condition of dental hard tissues in patients with mental illnesses. The paper examines the dental health characteristics of individuals suffering from psychoses, depression, schizophrenia, and other mental disorders. Such patients often face challenges in maintaining oral hygiene, improper nutrition, and the side effects of medication, which contribute to the deterioration of dental tissues. The study used methods such as clinical dental examination, radiographic analysis, and patient surveys to assess the state of teeth and gums. The results revealed a higher prevalence of dental caries, periodontal diseases, and enamel defects in this group, highlighting the impact of mental health conditions and associated treatments on oral health. This research underscores the importance of regular dental care and proper oral hygiene education for individuals with mental disorders.